Isoniazid-sensing Behavior of a Hybrid Silsesquioxane and Cobalt Pentacyanonitrosylferrate-based Nanocomposite - Souza Magossi, Mariana de [UNESP]; Souza Magossi, Maiara de [UNESP]; Dias Filho, Newton Luiz [UNESP]; Ribeiro do Carmo, Devaney [UNESP] (Wiley-Blackwell, 2021)
A novel silsesquioxane and cobalt nitroprusside compound was prepared from octa(aminopropyl)silsesquioxane, resulting in a nanocomposite (ACCoN), which was then characterized by different spectroscopic techniques. The cyclic voltammograms of the ACCoN-modified graphite paste electrode indicated a redox pair with a formal potential (E-theta ')=0.38 V, assigned to the (CoFe(II))-Fe-(II)(CN)(5)NO/(CoFe(III))-Fe-(II)(CN)(5)NO redox couple. The ACCoN-modified graphite paste electrode was sensitive to isoniazid concentrations, presenting a linear response at a concentration range from 6.0x10(-7) to 1.0x10(-5) mol L-1, with limit of detection and amperometric sensitivity of 5.53x10(-7) mol L-1 and 0.17 A/mol L-1, respectively.
Keywords: Silsesquioxanes; Cobalt pentacyanonitrosylferrate; Electrochemical sensing; Nanostructures